Intestinal malformation Small bowel atresia: three observations - Rosa, Folco (Cirugía del Uruguay, 2021)
Three observations, with different evolntion, of intestinal malformation, atre sia of the small intestine, are presented. In the first case, a jejunotransversotomy was performed, after the resection of the ileon, caceum and ascending colon. Because of the extent of the resection and the fact that the caecum was included, the intestinal zones more apt for absortion were suppressed. Perhaps it would have been beneficia} to make an inversion of a jejunal loop in order to form a sort of physiological valve for slowing up intestinal traffic. The child died two months lntér in a condition of virtual decomposition. The second case .of resection of the proximal intestinal segment made during a reoperation, indicated that this should have been performed during the first surgery. Details to support this point of view are supplied. A third tewlyborn child died in the immediate post-operatory period. According to the data funished by the autopsy, the most important alterations appeared at the lung level. Finally, stress is laid on the importance for the surgery of the newborn child, of the contribution of the pediatrician and an efficient nursing staff.